EFEKTIVITAS PARTISIPASI ORANGTUA DALAM KEGIATAN BELAJAR SISWA TERHADAP PRESTASI BELAJAR (Studi Deskriptif Terhadap Siswa Kelas XI IPS SMA BPI Kota Bandung) - Ria Ambarita Siregar (QUANTA, 2017)
Parental participation plays important role in improving the quality of student learning. The role or participation of parents give good influence and affects teacher's assessment towards students. Parents have a role to play in determining initiatives, structured activities at home to complete school education programs as they take place in Indonesia. Cavanagh and Romanoski (2005) argue that parents 'involvement in their children's education is an important aspect of school culture and schools need to make efforts so as to make students' parents have an increasingly bigger role in schools.